SCHEME FOR ADVANCING ACCESS TO BUSINESS FINANCES FOR MICRO ENTERPRISES IN TUTULO VILLAGE, BOTUMOITO DISTRICT, BOALEMO REGENCY - sukmawati muksin; azis rachman; sukrianto (Journal of Economic, Business, and Administration (JEBA), 2022)
The goal of this study is to identify a strategy for boosting microenterprise access to financing in Tutulo Village, Botumoito District, Boalemo Regency. The study employs descriptive qualitative approaches, including observation, indepth interviews, documentation, and SWOT analysis. The findings indicate that Micro Enterprises' strategies to increase access to business capital after assessing their strengths, weaknesses, opportunities, and threats are as follows: measuring consumer satisfaction with products and services, expanding business networks, and increasing pricing potential. Inexpensive, consumer-facing skill development. Promoting business products to individuals from beyond the region and increasing innovation by exploring micro-enterprises potential, maximizing promotional efforts, attracting personnel who understand how to use EMKM principles, and providing human resource management training. Consumer interest in business products is increasing. Business product innovation, volume discounts for bulk purchases, and regular checks on business items. Increased product innovation for local product variants, expansion of business items to meet consumer needs, and intensified promotional activity.